Consequences of the vaping epidemic on adolescents. Issue 7 (July 2020) - Patterson, Michelle; Williams-Jones, Pamela; Lewis, Travis "Pete"
Abstract : Abstract: The prevalence of vaping has seen a dramatic increase in the last decade, especially among adolescent populations. This article discusses the background, prevalence, and associated risk factors of e-cigarettes. Abstract : The prevalence of vaping has increased dramatically in the last decade, especially among adolescents. The authors discuss the background, prevalence, and health risks associated with vaping in this population.